Species‐specific germination responses to fire‐associated heat of elephant‐dispersed seeds in Nimule National Park, South Sudan. (6th April 2018) - Lado, Thomas F.; Jibi, Wani F.; Moilinga, Pasquale T.
Abstract: Fire‐related heat and endozoochory by elephants have independently been found to be important for savanna plant seed germination, yet there is little information on how heat affects germination of elephant‐dispersed seeds. We measured the germination behavior (time to germination and proportion of seeds germinating) of 11 species of seeds extracted from African savanna elephant dung and subjected them to various intensities of heat as a proxy for fire exposure. The effects of heat were inconsistent and varied significantly by species, with some species having increased time to germination in response to heat and others having reduced time to germination. More studies are needed to expand the number of seed species examined and tease apart the interaction between elephant‐mediated endozoochory and fire.